Synthesis and Characterization Titanium Dioxide (TiO2) Doped Vanadium(V) Using Solid State Method - Mustofa, Khusnan; Aini, Nur; Khalifah, Susi Nurul (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2015)
TiO2 Anatase activities should be increased from the UV to the visible light photocatalytic activity of TiO2 to increase anatas. One efforts to optimize TiO2 anatase activity is doping by using dopant vanadium(V). Synthesis method which is used in this research is a solid reaction method. The steps being taken in this methods include grinding and heating at high temperatures. Dopant concentrations of vanadium(V) which are used in the research was 0.3%, 0.5% and 0.7%. and the characterization used is X-ray diffraction and UV-Vis Diffuse Reflectance Spectroscopy. The result shows that there are a changing of particle size, band gap energy, and absorption of TiO2 anatas wavelength because of dopan vanadium(V) addition. While TiO2â€™s structure does not change. The crystal sizes of each TiO2 without doping, V-TiO2 0,3%, 0,5% and 0,7% are 53.21 nm, 47.67 nm, 79.65 nm dan 68.99 nm. Â Band gap energy of each TiO2 without doping, V-TiO2 0,3%, 0,5% dan 0,7% are 3.309 eV, 3.279 eV, 3.270 eV and 3.259 eV. While wavelength absorption of each TiO2 without doping, V-TiO2 0,3%, 0,5% and 0,7% are 374.9 nm, 378.4 nm, 379.5 nm and 380.8 nm. Â Keywords: Synthesis, titanium dioxide, vanadium(V), solid state method